Bimodality of Lavas in the Teide-Pico Viejo Succession in Tenerife--the Role of Crustal Melting in the Origin of Recent Phonolites - Wiesmaier, Sebastian; Troll, Valentin R.; Carracedo, Juan Carlos; Ellam, Robert M.; Bindeman, Ilya; Wolff, John A. (Journal of Petrology, 2012)
In Tenerife, lavas of the recent Teide–Pico Viejo central complex show a marked bimodality in composition from initially mafic lavas (200–30 ka) to highly differentiated phonolites (30–0 ka). After this abrupt change, the bimodality of the lavas continued to manifest itself between the now felsic Teide–Pico Viejo central complex and the adjacent, but exclusively mafic, rift zones. Whole-rock trace element fingerprinting distinguishes three compositional groups (mafic, transitional, felsic). Groundmass Sr–Nd–Pb–O and feldspar δ18O data demonstrate open-system behaviour for the petrogenesis of the Teide–Pico Viejo felsic lavas by high 87Sr/86Sr ratios of up to 0·7049, uniform 206Pb/204Pb (19·75–19·78), variable 207Pb/204Pb (15·53–15·62) and heterogeneous δ18O values (5·43–6·80‰). However, ocean sediment contamination can be excluded because of the low 206Pb/204Pb ratios of North Atlantic sediments. Isotope mixing hyperbolae reproduce the entire Teide–Pico Viejo succession and require an assimilant of predominantly felsic composition. Unsystematic and heterogeneous variation of δ18O in fresh and unaltered feldspars across the Teide–Pico Viejo succession indicates magmatic addition of diverse δ18O assimilants, altered near surface at high and low temperatures. The best fit for these requirements is provided by nepheline syenite that occurs as fresh or altered lithic blocks in voluminous pre-Teide ignimbrite deposits and is similarly heterogeneous in oxygen isotope composition. Nepheline syenite blocks are considered to represent deep remnants of associated earlier eruptions and were thus available for assimilation at depth. Rare earth element modelling indicates that nepheline syenite needs to be melted in bulk to form a suitable end-member composition. Using this assimilant, energy-constrained assimilation fractional crystallization (EC-AFC) modelling reproduces the bulk of the succession, which leads us to suggest that Teide–Pico Viejo petrogenesis is governed by assimilation and fractional crystallization. Both ...